PENGARUH TINGKAT LIKUIDITAS, SIMPANAN DANA PIHAK KETIGA, DAN JUMLAH KREDIT YANG DISALURKAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PADA PERIODE 201 –2015 - Stan ley; Purnama Yanti Purba; Jayanti Mandasari Hutapea; Har vin (Jurnal Akrab Juara, 2019)
The purpose of this study was to test the effect of the level of liquidity, third party deposits and total outstanding loans on profitability of banking companies listed in Indonesia Stock Exchange in the period of 2011-2015. Recently, economy situation in Indonesia was not good, but if you see the report of some financial banking companies in Indonesia, as if it did not affect the company, while some phenomena showed that the increased liquidity levels was not always followed by a decrease in profitability and an increase in third party deposits and total outstanding loans were not always followed by an increase in profitability. These are the reason to motivate the researcher to conduct this research. Population of the study were all banking companies listed in Indonesia Stock Exchange during the period of 2011-2015 consisting of 36 companies.The samples were taken by purposive sampling technique. Analysis method is multiple linear regression. The research result on the hypothesis revealed that partially T- test showed that the level of liquidity and third party deposits had a positive effect, but only a third party deposits which had a significant effect, while the number of loans showed a negative and significant effect on profitability, and simultaneously, F test showed that the level of liquidity, third party deposits and total loans shoed a positive and significant effect on profitability.